Randomized Controlled Trial of Laparoscopic versus Open Radical Cystectomy in a Laparoscopic Naïve Center - Waleed Mohamed Fadlalla; Ayman Hanafy; Mahmoud Abdelhakim; Hatem Aboulkassem; El Sayed Ashraf; Ahmed Abdelbary (Advances in Urology)
Background. Laparoscopic radical cystectomy is a challenging surgical procedure; however, it has been largely abandoned in favor of the more intuitive robotic-assisted cystectomy. Due to the prohibitive cost of robotic surgery, the adoption of laparoscopic cystectomy is of relevance in low-resource institutes. Methodology. This is a randomized controlled trial comparing laparoscopic radical cystectomy (LRC) to open radical cystectomy (ORC) at a single institute. Each group included thirty patients. The trial was designed to compare both approaches regarding operative time, blood loss, transfusion requirements, length of hospital stay, time to oral intake, requirement of opioid analgesia, and complications. Results. LRC was associated with less hospital stay (9.8 vs. 13.8 days, P=0.001), less time to oral solid intake (6 vs. 8.6 days, P=0.031), and lower opioid requirements (23.3% vs. 53.3%, P=0.033). There was a trend towards lower blood loss and transfusion requirements, but this did not reach statistical significance. Overall complication rates were comparable. Conclusion. Laparoscopic radical cystectomy was associated with comparable postoperative outcomes when compared to ORC in the first laparoscopic cystectomy experience in our center. Benefitting from the assistance of an experienced laparoscopic surgeon is recommended to shorten the learning curve.